Influence of EM4 Inoculum on Biogas Yield and pH Dynamics in Lettuce and Cabbage Waste Fermentation - Ramadhan, Dwi Sapri; Safitri, Wulan Dwi; Wardana, Dian; Fahmi, Jam'an; Zubir, Moondra; Andini, Ayu; Simamora, Elisabeth; Limbong, Julian; Sihotang, Pelita; Husna, Wiki Nadia; Siregar, Nurdin (Universitas Negeri Medan, 2025)
Biogas production from vegetable waste offers a practical pathway for reducing organic residues and supporting small-scale renewable energy systems. This study investigates the influence of EM4 inoculum on gas accumulation and pH dynamics during an 8-day batch fermentation of lettuce and cabbage waste. Four reactors were prepared containing 200 g vegetable waste and 200 mL water with or without 30 g EM4. Gas accumulation was quantified by balloon circumference at day 2, day 4, day 6 and day 8 and converted to volume using geometric calculations. Lettuce generated the highest peak volumes with maximum values exceeding 330 cm³ while cabbage produced less than 60 cm³ under comparable conditions. pH trajectories showed that cabbage plus water decreased from pH 7 to pH 6 whereas lettuce plus water increased from pH 7 to pH 8. Reactors containing EM4 stabilised at pH 6 throughout the fermentation indicating inoculum-supported buffering. These results demonstrate that substrate characteristics strongly influence early-stage gas formation and that EM4 moderates pH fluctuations even under uncontrolled ambient conditions. The findings provide initial evidence that lettuce is a more degradable feedstock than cabbage and emphasise pH regulation as a key requirement for improving methane-oriented biogas performance in simple batch systems.